2018
DOI: 10.1080/17434440.2018.1514257
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-based closure of aortic and mitral paravalvular leaks: existing techniques and new frontiers

Abstract: Significant paravalvular leak (PVL) complicates between 6% and 15% of valve replacements and can result in heart failure and hemolysis. Paravalvular leak can be effectively treated with repeat surgery; however, these procedures are associated with significant operative morbidity. Percutaneous PVL closure is increasingly being utilized as the first line therapy for symptomatic patients, but efficacy may be limited by the lack of dedicated closure devices. Areas covered: This article will review the etiology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Efforts are needed to develop new specifically designed devices to further improve clinical outcomes of this particular subset of high-risk patients with multiple comorbidities ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are needed to develop new specifically designed devices to further improve clinical outcomes of this particular subset of high-risk patients with multiple comorbidities ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Joseph et al . 8 reviewed techniques for percutaneous PVL closure and concluded that PVL closure is safe for most patients but associated with higher rates of residual leakage. Dedicated devices for PVL closure are needed to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PVL is about 6%–15%, 6 more common in mechanical prostheses and is reported to be around 2%–10% 7 in the aortic position. It is highly accepted that moderate‐to‐severe and severe PVL should be corrected as soon as possible, but as for mild‐to‐moderate or moderate PVL patients, there is no consensus regarding the optimal management 5 .…”
Section: Commentsmentioning
confidence: 99%
“…The incidence of PVL is about 6%-15%, 6 more common in mechanical prostheses and is reported to be around 2%-10% 7 in the aortic position. It is highly accepted that moderate-to-severe and…”
Section: Commentsmentioning
confidence: 99%